IMPLICATURE IN THE PROPOSAL MOVIE - Aprillia Miftaqul Wijiningtias; M Bahri Arifin; Ririn Setyowati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
The purposes of this research were to find out all utterances by the main characters Margaret Tate and Andrew Paxton that contains implicature and its context in The Proposal movie. This research was categorized as qualitative research and used content analysis approach. The researcher used The Proposal (2006) movie as the source of data. The data were taken from the utterances between the main characters Margaret Tate and Andrew Paxton that contained implicature based on implicature theory by Grice and its context used context theory by Hymes. The findings reveal that the researcher got 23 data of conversational implicature and 14 data of conventional implicature. 15 data from 23 data of conversational implicature are done by Andrew. From the data that the researcher found, component of the context that prominent between Andrew and Margaret was participants. From 15 data of conversational implicature done by Andrew, the contexts of participant are vertical dimension. Vertical dimension is a component that relates to social factors such as age or social status. The seven data of this research were vertical dimension of social status between Margaret as a boss and Andrew as her assistant. Then, the other eight data were social status of both of Margaret and Andrew as a fake lover. The context of participant in this research became the benchmark for the researcher to find the implied meaning.